Efektivitas Pelaksanaan Program Pemberdayaan Perempuan Kepala Keluarga (PEKKA) di Kabupaten Jombang - Utaminingsih, Alifiulahtin (Equalita: Jurnal Studi Gender dan Anak, 2023)
ABSTRACT: This research analyzes how and effectiveness the Empowerment of Women Headed of Families (PEKKA) program is an empowerment program that involves women as the main target. This program was first introduced in 2000 as a "widows project" by the National Commission on Violence Against Women. The aim is to facilitate the development of life skills or life skills that are useful for being independent. The skills carried out are of economic value to empower women heads of families (PEKKA) in Jombang Regency. The method used is qualitative with a descriptive approach. The aim of this research is to analyze the effectiveness of the PEKKA program by the Family Planning, Women and Child Protection Population Control Service (DP3KBP3A) to empower female heads of families in Jombang Regency. The theory used is the Empowerment Theory by Sarah Cook and Steve Mcauly with the effevtiveness of  PEKKA concept. Qualitative descriptive research method and purposive sampling, with research informants all PEKKA active members in Jombang Regency. The results of the research show that the PEKKA program has not been running well, the efforts made are through mentoring in various areas in Jombang Regency and socialization and educational approaches.Keywords: Effective, Empowerment of Women, Head of Family